Challenges of integrating HIV prevention and treatment in China's border mountain regions: a grounded theory study - Sixian Du; Haoran Niu; Feng Jiang; Liwen Gong; Shan Zheng; Qi Cui; Xu Yang; Jiayan He; Rongcai Dai; Qilian Luo; Yiqing Yang (BMC Infectious Diseases)
Abstract Background HIV remains a critical global public health challenge, with 39 million people living with HIV as of 2022 and over 40.4 million lives lost to the epidemic. In China, the burden is similarly significant, with over 1.33 million HIV cases reported as of 2024. The challenges are particularly acute in western regions like Yunnan Province, which face resource limitations, socio-demographic disparities, and a high prevalence of HIV among ethnic minorities. Objectives This study examines the challenges in HIV diagnosis, treatment, and prevention across various institutions in Yunnan Province, including government bodies, hospitals, disease control centers, and primary healthcare institutions. This study aims to identify key challenges in integrating HIV prevention and treatment in China’s border mountainous regions to inform targeted strategies for ethnic minority and impoverished communities. Methods This study adopts a grounded theory approach to explore the systemic, socio-demographic, and cultural barriers impeding the integration of HIV prevention and treatment in M City, a resource-constrained border region in Yunnan Province. From May 2024 to January 2025, a comprehensive review of regional HIV prevention and control literature, alongside relevant World Health Organization (WHO) guidelines, was undertaken to contextualize the research. To capture multi-level insights, semi-structured interviews were conducted between August and December 2024 with 23 purposively selected participants, including individuals living with HIV, village doctors, healthcare providers, and local policymakers. The qualitative data were analyzed through a rigorous three-stage coding process—comprising open coding, axial coding, and selective coding—consistent with grounded theory methodology, to systematically construct and refine conceptual categories underpinning the integration challenges. Results This study included 23 participants from Yunnan Province. Through three-level coding, three major themes were identified. In HIV prevention, key challenges included patients' inattention to prevention, difficulties for village doctors in home-based screening, and poor enthusiasm for prevention in hospitals. In HIV treatment, difficulties included limited government support, variability in patients' conditions, poor medication adherence, poor quality of village clinic services, challenges for healthcare staff, uncertain effects of Chinese and Western medicine synergy, and unsmooth referral mechanisms. In integration of HIV prevention and treatment, major issues involved low referral rates, loose inter-agency cooperation, and systemic barriers to integration. Conclusion This study highlights the complex challenges in HIV prevention, treatment, and integration in economically underdeveloped regions, emphasizing the need for improved patient awareness, healthcare system efficiency, and cross-institutional collaboration. Future research should focus on multi-center, longitudinal studies and real-world implementation to refine and scale the integration model for sustainable HIV care in these regions.